2017
DOI: 10.1111/ipd.12286
|View full text |Cite
|
Sign up to set email alerts
|

Can oral health education be delivered to high‐caries‐risk children and their parents using a computer game? – A randomised controlled trial

Abstract: Oral health education using a computer game can be as satisfactory and as effective in improving high-risk-children's knowledge as one-to-one education. The education received can lead to the positive dietary changes in some families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 25 publications
1
25
0
3
Order By: Relevance
“…Systematic reviews and meta-analyses of gamification, serious games, and apps about health topics found that they can have a positive impact on health and well-being in the general population [17-20]. Other gamification studies reported positive associations between gamification and school-aged knowledge in several health topics; a randomized controlled trial (RCT) of a serious game promoting oral health found a significant improvement in knowledge of children after playing the game compared with before playing the game [13]. Likewise, an RCT for a game educating children about asthma found an increase in knowledge and improved attitudes at postintervention and follow-up as compared with control [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews and meta-analyses of gamification, serious games, and apps about health topics found that they can have a positive impact on health and well-being in the general population [17-20]. Other gamification studies reported positive associations between gamification and school-aged knowledge in several health topics; a randomized controlled trial (RCT) of a serious game promoting oral health found a significant improvement in knowledge of children after playing the game compared with before playing the game [13]. Likewise, an RCT for a game educating children about asthma found an increase in knowledge and improved attitudes at postintervention and follow-up as compared with control [11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that gamification and serious games for health and well-being are most effective when targeting health-related behaviors [10]. For instance, positive associations between gamification, serious games, and school-aged knowledge and behavior have been reported in public health topics such as asthma [11], fruit and vegetable consumption [12], and oral hygiene [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, the use of digital technology was found to promote positive behavioral changes in patients with regard to adherence to oral hygiene practices. 24,26 For example, videos were reported to be an engaging and effective way to improve and reinforce a patient's oral health knowledge and maintenance of good oral habits. 27 Therefore, clinicians could create personalized oral hygiene instructional videos for their patients to encourage them to maintain good oral hygiene habits over time.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Essentially all of the children came from socially deprived backgrounds; the game helped children to identify sugary foods, and a concealed ‘trophy’ password at the end of it confirmed that 34 of them, the older children, had completed play and the families reported that they had found it to be a highly satisfactory method of receiving oral health education. The study did not report how other family characteristics influenced play at home …”
Section: Introductionmentioning
confidence: 99%
“…The study did not report how other family characteristics influenced play at home. 3 Another on-line game (WebTIPS) used to prepare children prior to tonsillectomy and adenoidectomy, aimed at reducing pre-operative child anxiety. However, it was not intended as a 'stand-alone' game; it was delivered in combination with parental coping skill instruction, and questionnaires about parental anxiety, preferences and choices of pre-medication and the child's coping preferences.…”
Section: Introductionmentioning
confidence: 99%